2001
DOI: 10.1177/156482650102200407
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Vitamin A Intake in Young Children in Western Kenya: Orange-Fleshed Sweet Potatoes and Women Farmers Can Serve as Key Entry Points

Abstract: In western Kenya, where vitamin A deficiency is common and the white sweet potato is an important secondary staple, orange-fleshed sweet potatoes were introduced and their consumption was promoted, along with other vitamin A-rich foods. Ten women's groups grew a number of varieties of sweet potato on group plots in on-farm trials. Five of the groups also received an intervention consisting of nutritional education, individual counseling, and participatory rapid appraisal techniques to promote vitamin A consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 11 publications
4
47
0
Order By: Relevance
“…In a community‐based project in Kenya, new varieties of orange‐fleshed sweet potato were introduced to women farmers. Children's dietary intake of vitamin A‐rich foods increased provided that factors contributing to good nutrition and gender constraints hindering access to technologies were addressed 58, 59…”
Section: Orange‐fleshed Sweet Potatomentioning
confidence: 99%
See 2 more Smart Citations
“…In a community‐based project in Kenya, new varieties of orange‐fleshed sweet potato were introduced to women farmers. Children's dietary intake of vitamin A‐rich foods increased provided that factors contributing to good nutrition and gender constraints hindering access to technologies were addressed 58, 59…”
Section: Orange‐fleshed Sweet Potatomentioning
confidence: 99%
“…In Kenya, for example, adults preferred sweet potato with a high dry matter content, while children preferred sweet potato with a low dry matter content 58 Crops, especially vegetables, grown by women are normally used for household consumption68 and should therefore be promoted in home‐gardens 58 A study in South Africa showed that most of the capital cost is spent on buying seeds 69.…”
Section: Home‐gardens To Address Vitamin a Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus growing and consuming vitamin A-rich crops can act as a vehicle for tackling VAD. Indeed, proof-concept studies and efficacy trials have demonstrated that consumption of modest amounts (125g a day) of orange-fleshed sweetpotato (OFSP), a biofortified crop, can supply the daily needs of vitamin A [1,12,13].…”
Section: The Concept Of Food Insecurity and Food-based Approach To Fimentioning
confidence: 99%
“…According to the survey conducted in six States in Nigeria by [7], the different forms of sweet potato utilization are boiling and eating with stew/palm oil, slicing and frying, roasting, boiling and eating as snack; boiling and pounding alone or with boiled yam/garri for eating with soup; cooking alone or with another crop to make pottage; slicing and sun-drying for milling into flour; feeding of vines and leaves to livestock; small tuberous roots as livestock feed; made into fufu like cassava; fresh leaves and young shoots consumed as vegetable. Also, in some African countries like Kenya, the storage roots are boiled and eaten, or chipped, dried and milled into flour which is then used to prepare snacks and baby weaning foods [8].…”
Section: Introductionmentioning
confidence: 99%